2020
DOI: 10.1080/07391102.2020.1784291
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of FDA-approved antivirals, antibiotics, anthelmintics, antioxidants, and cell protectives against SARS-CoV-2 papain-like protease

Abstract: SARS-CoV-2 or Coronavirus disease 19 (COVID-19) is a rapidly spreading, highly contagious, and sometimes fatal disease for which drug discovery and vaccine development are critical. SARS-CoV-2 papainlike protease (PL pro) was used to virtually screen 1697 clinical FDA-approved drugs. Among the top results expected to bind with SARS-CoV-2 PL pro strongly were three cell protectives and antioxidants (NADþ, quercitrin, and oxiglutatione), three antivirals (ritonavir, moroxydine, and zanamivir), two antimicrobials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 34 publications
1
73
2
Order By: Relevance
“…The SARS-CoV-2 is a zoonotic pathogen that belongs to the Betacoronavirus (β-CoV) genus of the Orthocoronavirinae subfamily of the Coronaviridae family [4]. Its genome is an enveloped, positive-sense, single-stranded genomic RNA (+ ssRNA; gRNA) of approximately 30 kilobases (kb) that shows 88-96% sequence identity to the bat coronaviruses bat-Cov RaTG13, bat-SLCoVZXC21 and bat-SL-CoVZC45 and 80% homology to the human SARS-CoV [1,5,6].…”
Section: Sars-cov-2mentioning
confidence: 99%
“…The SARS-CoV-2 is a zoonotic pathogen that belongs to the Betacoronavirus (β-CoV) genus of the Orthocoronavirinae subfamily of the Coronaviridae family [4]. Its genome is an enveloped, positive-sense, single-stranded genomic RNA (+ ssRNA; gRNA) of approximately 30 kilobases (kb) that shows 88-96% sequence identity to the bat coronaviruses bat-Cov RaTG13, bat-SLCoVZXC21 and bat-SL-CoVZC45 and 80% homology to the human SARS-CoV [1,5,6].…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Famotidine is an H2 antagonist and antiulcer agent with an optimal safety profile. In silico studies 66 , 67 revealed famotidine as a potential therapeutic agent against SARS-CoV-2 M pro 65 , 66 . Another study indicated that its effect is not the result of antiviral activity, but an anti-inflammatory action.…”
Section: Drug Repurposing For Sars-cov-2mentioning
confidence: 99%
“…(84,86,87,88,89,90) Putative inhibitors of SARS-CoV-2 PL pro include FDA-approved drugs such as fostamatinib disodium (6) (a tyrosine kinase inhibitor used in the treatment of chronic immune thrombocytopenia) and natural products [e.g., platycodin D (7)]. (89,91) RNA-dependent RNA polymerase (RdRp, Nsp12) is an essential protein responsible for RNA synthesis during viral RNA transcription and replication cycles. (89) As described for SARS-CoV, the RNA polymerase activity of SAR-CoV-2 RdRp (804 aa) also seems to require the binding of Nsp7 and Nsp8 cofactors to enhance RdRp binding and processivity.…”
Section: Sars-cov-2: Structure Mechanism Of Infection and Drug Targetsmentioning
confidence: 99%